Translation techniques used by English Department students of Universitas Negeri Padang in translating a narrative text - Ika Wellya Rahesa Rm; Rusdi Noor Rosa (English Language and Literature, 2020)
Translation is an activity that plays a very important role in acquiring information that comes from a foreign language. In translating a text, every translator will certainly encounter several problems such as vocabulary, grammar, and culture in the target language (TL). One of the ways to solve such problem is using translation techniques, and different problems need different techniques. this study is aimed at: finding out the techniques used by the third year English Department students in translating a narrative text from English into bahasa Indonesia. Based on the results of data analysis, it was found that the translation of narrative text entitled “Snow White” from English into bahasa Indonesia done by the third year students of English Department of Universitas Negeri Padang uses nine translation techniques. They are literal translation, established equivalent, discursive creation, amplification, generalization, adaptation, borrowing, modulation, and linguistic compression.